EXPLORING THE ROLE OF JOB RESOURCES IN THE WELL-BEING OF WOMEN ACADEMICS IN THE WORKPLACE - Maboeta, Bonita; van Schalkwyk, Izanette; Bloem, Retha (Social Work, 2023)
Despite several changes in the workplace, women still face unique challenges with harmful effects on their well-being. Job resources are a crucial buffer between job demands and workplace well-being. The aim of this article is to present the findings of a qualitative study on women academics’ experiences of workplace well-being in relation to job resources. An exploratory and descriptive research design was used to investigate in what ways job resources contribute to women academics’ perceptions of workplace well-being. Purposive sampling was conducted at a top-rated university in South Africa. Data were gathered through twelve semi-structured interviews. Findings revealed that women academics value a variety of job resources associated with psychological, social, physical, and organisational resources. The study also revealed the inherent job resources creating strains on women’s well-being in the workplace. It is recommended that higher education institutions focus on workplace well-being from a practice, organisational, and policy perspective. Keywords: conservation of resources, job demands-resources model, strengths perspective, South Africa, job resources, well-being, women in academia